ETIKA PERCERAIAN DALAM QS. AL-THALAQ DAN IMPLIKASINYA SECARA TEOLOGIS SERTA SOSIOLOGIS - Isti Parida; Lukman Nul Hakim; Almunadi (Al-Shamela : Journal of Quranic and Hadith Studies, 2023)
This article aims to discuss the ethics of divorce in QS. al-Thalaq which have theological and sociological implications. By using the type of research library research and thematic interpretation method (maudhu'i) by taking one letter, namely QS. al-Thalaq, this article concludes that the ethics of divorce in QS. There are 4 al-Thalaq, namely: (1) the husband drops divorce when the wife is pure from menstruation and has not been interfered with; (2) Allah forbids the believers to take the divorced wife out of the house before her iddah runs out; (3) The iddah of a woman who is not old enough (not yet an adult) is that she has never had menstruation; and (4) the iddah of an elderly woman, namely three months, while for a woman who is pregnant and her husband has died, her iddah is until she gives birth to the baby she is carrying. The theological implications of QS. al-Thalaq includes: confidence in Allah's help and confidence in His sustenance. While the sociological implications include: divorce can solve household life problems, does not break friendships and is included in the destiny of a mate.